Sulfide-based solid electrolyte, method for producing sulfide-based solid electrolyte, and all-solid-state battery comprising sulfide-based solid electrolyte
By adopting glass-ceramic sulfide-type solid electrolytes with type II crystal phase of the thio-LISICON region, the problems of low stability of sulfide-type solid electrolytes to lithium metal and low conductivity of lithium ion are solved, high lithium ion conductivity and stability are achieved, and the commercialization of all-solid-state batteries is promoted.
Patent Information
- Application Number
- CN202480003937.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2024-02-14
- Publication Date
- 2025-04-18
AI Technical Summary
The sulfide-based solid electrolyte has low stability to lithium metal, and the poor framework structure of P2S64- contained reduces the lithium ion conductivity.
A glass ceramic sulfide-based solid electrolyte containing a thio-LISICON region type II crystal phase is prepared by sintering a mixture of lithium source, phosphorus source, sulfur source and halogen source at a temperature of 150°C to 250°C.
It improves lithium ion conductivity, enhances the stability of lithium metal negative electrodes, and realizes a high-quality energy density all-solid-state battery.
Smart Images

Figure CN119856318A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sulfide-based solid electrolyte, a method for preparing the sulfide-based solid electrolyte, and an all-solid-state battery comprising the sulfide-based solid electrolyte.
[0002] This application claims priority from Japanese Patent Application No. 2023-023528, filed on February 17, 2023, the disclosure of which is incorporated herein by reference. Background Art
[0003] In order to achieve higher safety, longer life and higher energy density, all-solid-state batteries using solid electrolytes instead of liquid electrolytes of lithium-ion batteries have been developed. Among the many solid electrolytes, sulfide solid electrolytes (such as Li 10 GeP2S 12 ) has an ionic conductivity as high as that of liquid electrolytes and is easy to come into close contact with soft active materials, so all-solid-state batteries using sulfide solid electrolytes are expected to be commercialized.
[0004] Lithium metal has attracted much attention as anode material for all-solid-state batteries due to its light weight per unit volume and high theoretical capacity, which can improve mass energy density (Wh / kg). 10 GeP2S 12 ) has low stability to lithium metal and is therefore difficult to use with lithium metal anodes.
[0005] In order to solve this problem, Patent Documents 1 to 3 disclose glass-ceramic sulfide-based solid electrolytes that are stable to lithium metal.
[0006] However, the P2S6 contained in the sulfide solid electrolyte 4- The poor skeleton structure reduces the lithium ion conductivity of sulfide-based solid electrolytes.
[0007] [Related technical literature]
[0008] [Patent Document]
[0009] Patent Document 1: Japanese Patent Application Publication No. 2015-011898
[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-100907
[0011] Patent Document 3: WO 2019 / 098245 Summary of the invention
[0012] Technical issues
[0013] The present disclosure relates to providing a sulfide-based solid electrolyte having improved lithium ion conductivity, a method for preparing the sulfide-based solid electrolyte, and an all-solid-state battery including the sulfide-based solid electrolyte.
[0014] Technical Solution
[0015] In order to achieve the above-mentioned object, the present disclosure provides a sulfide-based solid electrolyte comprising a sulfo-LISICON region II type crystalline phase, wherein the sulfide-based solid electrolyte is a glass ceramic, wherein the sulfide-based solid electrolyte is represented by a chemical formula (100-x){(0.75+y / (100-x))Li2S-0.25P2S5}-xLiHa, wherein in the chemical formula, Ha is at least one selected from halogen elements, and wherein 15≤x≤30 and 0 are satisfied. <y<2.25。
[0016] In one embodiment, x may satisfy 23≤x≤27.
[0017] In one embodiment, y may satisfy 0.2 <y<0.4。
[0018] In one embodiment, Ha may include Br.
[0019] In one embodiment, I1 / I2<0.06 may be satisfied. Here, I1 is the wavelength at 380 cm in the Raman spectrum. -1 Up to 400cm -1 The intensity of the peak detected at 415 cm in the Raman spectrum is I2. -1 Up to 425cm -1 The intensity of the peak detected at .
[0020] The present disclosure provides a method for preparing a sulfide-based solid electrolyte as defined in any one of the above embodiments, the method comprising: mixing a lithium source, a phosphorus source, a sulfur source, and a halogen source to obtain a mixture; and sintering the mixture at a temperature of 150°C to 250°C.
[0021] The present disclosure provides an all-solid-state battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer, wherein the solid electrolyte layer comprises a sulfide-based solid electrolyte defined in any one of the above embodiments.
[0022] Beneficial Effects
[0023] The present disclosure may provide a sulfide-based solid electrolyte having improved lithium ion conductivity, a method for preparing the sulfide-based solid electrolyte, and an all-solid-state battery including the sulfide-based solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 X-ray diffraction (XRD) patterns of Examples and Comparative Examples are shown.
[0025] Figure 2 is a graph showing changes in lithium ion conductivity depending on the composition of the sulfide-based solid electrolyte.
[0026] Figure 3 The Raman spectra of Example 2, Comparative Example 1, and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0027] Hereinafter, the present disclosure will be described in more detail.
[0028] It should be understood that the words or terms used in the specification and the appended claims should not be interpreted as limited to the ordinary meaning and dictionary meaning, but should be interpreted based on the meaning and concepts corresponding to the technical aspects of the present disclosure based on the principle of allowing the inventor to appropriately define the terms to obtain the best interpretation.
[0029] [Solid electrolyte for all-solid-state batteries]
[0030] The solid electrolyte for all-solid-state batteries disclosed herein may include at least one of a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte. Preferably, the solid electrolyte for all-solid-state batteries disclosed herein is a sulfide solid electrolyte. The solid electrolyte for all-solid-state batteries may be mixed with a positive electrode mixture material and used as a positive electrode material, or may be mixed with a negative electrode mixture material and used as a negative electrode material, and may also be used as a separator. The solid electrolyte for all-solid-state batteries may also include additives such as lithium salts, conductive materials, and binder resins according to the purpose of use.
[0031] <Sulfide solid electrolyte>
[0032] The sulfide-based solid electrolyte may include any sulfur-containing sulfide-based solid electrolyte commonly used in the art, but is not limited thereto. The sulfide-based solid electrolyte may be amorphous, glass, or glass ceramic.
[0033] In the present disclosure, the sulfide-based solid electrolyte is a glass ceramic. The glass-ceramic sulfide-based solid electrolyte has high stability to lithium metal, which enables the use of lithium metal with high mass energy density as a negative electrode material. Glass ceramic is a glass containing deposited crystallites in the glass by heat-treating the glass, also known as crystallized glass. Since the crystallites promote lithium ion conduction, the glass-ceramic sulfide-based solid electrolyte containing crystallites that promote lithium ion conduction can have high lithium ion conductivity.
[0034] Non-limiting examples of sulfide-based solid electrolytes may include at least one of Li2S-P2S5, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SnS, Li2S-P2S5-Al2S3, Li2S-GeS2, or Li2S-GeS2-ZnS. However, the sulfide-based solid electrolyte is not particularly limited thereto.
[0035] In the present disclosure, the sulfide-based solid electrolyte contains a sulfo-LISICON region II type crystalline phase. The sulfide-based solid electrolyte may also contain other crystalline phases, such as Li3PS4 crystalline phase, Li4P2S6 crystalline phase, Li7PS6 crystalline phase and Li7P3S 11 Crystalline phase. The thio-LISICON domain II type crystal phase may have high lithium ion conductivity, and a sulfide-based solid electrolyte containing the crystal phase may have high lithium ion conductivity.
[0036] The proportion of the crystalline phase (referred to as "crystal structure" in this specification) contained in the sulfide solid electrolyte can be quantitatively or non-quantitatively evaluated based on the X-ray diffraction (XRD) spectrum. One method is to evaluate the proportion of the crystalline phase by comparing the peak intensity of the XRD spectrum. The peak intensity can be evaluated based on height or area. By XRD measurement, the sulfo-LISICON region II type crystalline phase was observed at 2θ = 20.3 ± 0.5°, 23.5 ± 0.5°, and 29.6 ± 0.5° of the XRD spectrum.
[0037] The sulfide-based solid electrolyte may contain an impurity phase. The impurity phase may include a crystalline phase or an amorphous phase, such as a Li2S phase, a P2S5 phase, a LiI phase, a LiBr phase, and a Li3PS4 phase. The impurity phase may reduce the lithium ion conductivity of the sulfide-based solid electrolyte, and preferably contains a small amount of the impurity phase or does not contain the impurity phase.
[0038] In the present disclosure, the sulfide-based solid electrolyte is represented by the chemical formula (100 - x){(0.75 + y / (100 - x))Li2S - 0.25P2S5} - xLiHa. In the above chemical formula, Ha is at least one selected from halogen elements, 15 ≤ x ≤ 30, and 0 < y < 2.25. As the composition of the sulfide-based solid electrolyte, Li2S(67%) - P2S5(33%), Li2S(70%) - P2S5(30%), and Li2S(75%) - P2S5(25%) (molar ratio) are known. The sulfide-based solid electrolyte of the present disclosure has the following designed composition: based on the molar ratio of Li2S and P2S5 of 3:1, Li2S(75%) - P2S5(25%), containing an excess of Li2S and lithium halide (LiHa). The sulfide-based solid electrolyte having this designed composition can have high lithium ion conductivity.
[0039] In the above chemical formula, x represents the amount of lithium halide (LiHa) in the sulfide-based solid electrolyte. x satisfies 15 ≤ x ≤ 30. Preferably, x can satisfy 23 ≤ x ≤ 27. More preferably, x can satisfy 24 ≤ x ≤ 26. More preferably, x can satisfy x = 25. When x satisfies the above range, the lithium halide can suppress P2S6 4- from the influence of the bad framework structure, and the sulfide-based solid electrolyte can have high lithium ion conductivity.
[0040] In the above chemical formula, y represents the excess Li2S. y satisfies 0 < y < 2.25. y can satisfy 0.14 < y < 0.56. Preferably, y can satisfy 0.2 < y < 0.4. More preferably, y can satisfy 0.25 ≤ y ≤ 0.35. More preferably, y can satisfy 0.26 ≤ y ≤ 0.30. When y satisfies the above range, the excess Li2S can suppress the formation of the bad framework structure of P2S6 4- and the sulfide-based solid electrolyte can have high lithium ion conductivity. When y = 0, the formation of the bad framework structure cannot be suppressed. When y ≥ 2.25, too much Li2S promotes the formation of the bad framework structure, so the effect of improving the lithium ion conductivity cannot be achieved.
[0041] In the above chemical formula, halogen (Ha) is at least one selected from the halogen elements. Halogen (Ha) may include chlorine (Cl), bromine (Br) and iodine (I). Preferably, halogen (Ha) may include bromine (Br). When sulfur in the sulfide solid electrolyte is a divalent anion, it attracts lithium ions more strongly than monovalent halogens, significantly hindering the movement of lithium ions. In particular, the inclusion of bromine (Br) as a halogen can result in a low sulfur (S) occupancy rate at a specific site in the sulfide solid electrolyte, a high halogen occupancy rate at the corresponding site, and a high lithium ion mobility near the bromine (Br) site. As a result, lithium ion conductivity can be improved. In addition, bromine (Br) combines with Li in the sulfide solid electrolyte to form a water-absorbing material lithium bromide (LiBr). Lithium bromide (LiBr) absorbs moisture that can reduce lithium ion conductivity, thereby further improving the lithium ion conductivity of the sulfide solid electrolyte.
[0042] The skeleton structure of sulfide solid electrolytes, such as PS4 3- (tetrahedron), P2S7 4- (two PS4 tetrahedrally connected dimer units) and P2S6 4 The presence of S in the dimer unit (i.e., dimer unit with S vacancies) can be quantitatively or non-quantitatively evaluated by Raman spectroscopy. -1 Up to 400cm -1 P2S6 detected at 4- The skeleton structure, whose peak intensity is represented by I1. -1 Up to 425cm -1 PS4 detected 3- The peak intensity of the skeleton structure is represented by I2. In the present disclosure, the peak intensity is evaluated based on the height. P2S6 4- The proportion of the backbone structure can be quantitatively assessed by evaluating the peak intensity ratio I1 / I2. 4- The framework structure can reduce the lithium ion conductivity due to S vacancies.
[0043] Preferably, the sulfide-based solid electrolyte of the present disclosure may satisfy a peak intensity ratio I1 / I2 < 0.06. More preferably, the peak intensity ratio I1 / I2 ≤ 0.03, more preferably I1 / I2 ≤ 0.01, and most preferably I1 / I2 = 0. When the peak intensity ratio I1 / I2 satisfies the above range, the sulfide-based solid electrolyte contains little or no P2S6 that reduces lithium ion conductivity. 4- The framework structure, therefore, can have high lithium ion conductivity.
[0044] Unless otherwise specified, the lithium ion conductivity of the sulfide solid electrolyte (also referred to as "ion conductivity" in the specification) refers to the lithium ion conductivity at room temperature (25°C, 298K) and atmospheric pressure (1atm). When the sulfide solid electrolyte is used in an all-solid-state battery, in practice, the lithium ion conductivity is preferably 4mS / cm or more. The lithium ion conductivity of the sulfide solid electrolyte disclosed in the present invention is 2.4mS / cm or more, preferably 2.9mS / cm or more, more preferably 4mS / cm or more, more preferably 5mS / cm or more, and most preferably 5.5mS / cm or more.
[0045] The sulfide-based solid electrolyte of the present disclosure can be obtained by a preparation method including the steps of: mixing a lithium source, a phosphorus source, a sulfur source, and a halogen source to obtain a mixture; and sintering the mixture at a temperature of 150° C. to 250° C. under an inert atmosphere (e.g., argon and nitrogen). The step of obtaining the mixture and the step of sintering the mixture can be performed in an inert gas atmosphere, such as argon and nitrogen.
[0046] The lithium source, phosphorus source, sulfur source and halogen source can be compounds, such as sulfides, oxides or nitrides. Lithium sulfide (Li2S) can be used as a lithium source, phosphorus pentasulfide (P2S5) can be used as a phosphorus source, and lithium halides (LiHa) such as lithium bromide (LiBr) and lithium iodide (LiI) can be used as halogen sources. In addition, sulfur can be supplied by other element sources. That is, at least one of a lithium source, a phosphorus source or a halogen source can also be used as a sulfur source.
[0047] The step of obtaining the mixture is to mix and grind the raw materials (i.e., lithium source, phosphorus source, sulfur source, and halogen source) to make them amorphous-glassy. The step of obtaining the mixture can be carried out using a mechanical grinder known in the corresponding field. The mechanical grinder can include a ball mill, a bead mill, a vibrator, and a grinder. The conditions of the mechanical grinder (e.g., rotation speed, time, and frequency) can be appropriately set by those skilled in the art to make the raw materials amorphous-glassy.
[0048] The sintering step is a step of crystallizing at least part of the amorphous-glassy mixture to form a glass ceramic. The sintering temperature is 150°C to 250°C. Preferably, the sintering temperature is 170°C to 230°C, more preferably 180°C to 220°C. When the sintering temperature satisfies the above range, the formation of the sulfo-LISICON region II type crystalline phase can be promoted, thereby obtaining a glass ceramic sulfide solid electrolyte. Since the sulfo-LISICON region II type crystalline phase has high lithium ion conductivity, the sulfide solid electrolyte containing the crystalline phase can have high lithium ion conductivity.
[0049] [All-solid-state battery]
[0050] The all-solid-state battery electrolyte disclosed herein can be used in an all-solid-state battery containing a positive electrode, a negative electrode and a solid electrolyte layer. The all-solid-state battery solid electrolyte can be used together with the active material in the electrode active material layer of the positive electrode and the negative electrode. The all-solid-state battery solid electrolyte can be used as a material for the solid electrolyte layer. The all-solid-state battery electrolyte can control the average particle size according to the purpose of use. The lithium ion conductivity can be improved by controlling the average particle size of the all-solid-state battery electrolyte.
[0051] <Solid Electrolyte Layer>
[0052] In the present disclosure, the thickness of the solid electrolyte layer may be about 50 μm or less, preferably about 15 μm to 50 μm. Within the above range, the solid electrolyte layer may have an appropriate thickness in consideration of the lithium ion conductivity, mechanical strength or energy density of the battery to which it is applied. For example, in terms of lithium ion conductivity or energy density, the thickness may be greater than 10 μm, greater than 20 μm, or greater than 30 μm. At the same time, in terms of mechanical strength, the thickness may be less than 50 μm, less than 45 μm, or less than 40 μm. In addition, in addition to the above thickness range, the tensile strength of the solid electrolyte layer may be about 100 kgf / cm 2 To about 2000kgf / cm 2 In addition, the porosity of the solid electrolyte layer may be about 15% by volume or less or about 10% by volume or less. For example, the porosity may be evaluated by water immersion porosimetry. As described above, the solid electrolyte layer of the present disclosure is a thin film, but may have high mechanical strength.
[0053] <Positive and negative electrodes>
[0054] In the present disclosure, the positive electrode and the negative electrode include a current collector and an electrode active material layer located on at least one surface of the current collector, and the electrode active material layer includes a plurality of electrode active material particles and a solid electrolyte. In addition, if necessary, the electrode may further include at least one of a conductive material or a binder resin. In addition, the electrode may further include various additives to supplement or improve the physical and chemical properties of the electrode.
[0055] In the present disclosure, the negative electrode active material may include any type of negative electrode active material for lithium ion secondary batteries. For example, the negative electrode active material may include at least one selected from the following: carbon, such as non-graphitized carbon, graphitized carbon; metal composite oxide, such as Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8); lithium metal; lithium alloy; silicon metal; silicon-based alloy; indium metal; indium alloy; tin-based alloy; metal oxides, such as: SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers, such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides. In a specific embodiment, the negative electrode active material may include carbon-based materials and / or Si.
[0056] In the case of the positive electrode, the electrode active material may include, but is not limited to, any type of positive electrode active material for a lithium ion secondary battery. For example, the positive electrode active material may include: layered compounds, such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; a lithium manganese oxide having the chemical formula Li 1+x Mn 2-x O4 (x is from 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; a Ni-site type lithium nickel oxide represented by the chemical formula LiNi 1-x A x O2 (A = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3); a lithium manganese composite oxide represented by the chemical formula LiMn 2-x A x O2 (A = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1) or Li2Mn3AO8 (A = Fe, Co, Ni, Cu or Zn); a spinel-structured lithium manganese composite oxide represented by LiNi x Mn 2-x O4; an NCM-based composite oxide represented by Li(Ni a Co b Mn c )O2 (a, b, c are each independently the atomic fraction of the element, 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1); LiMn2O4 in which Li in the chemical formula is partially substituted by alkaline earth metal ions; disulfide compounds; Fe2(MoO4)3, but not limited thereto.
[0057] In the present disclosure, according to the polarity of the battery, the current collector may include any suitable conductive current collector known in the field of secondary batteries, such as a metal plate.
[0058] In the present disclosure, the conductive material is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the mixture containing the electrode active material. The conductive material is not limited to a specific type and may include any material having conductivity without causing any chemical changes in the corresponding battery. For example, the conductive material may include one selected from the following: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder, nickel powder; conductive whiskers, such as zinc oxide, potassium titanate; conductive metal oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; or mixtures thereof.
[0059] In the present disclosure, the binder resin is not limited to a specific type and may include those that contribute to the bonding of the active material to the conductive material and to the current collector. For example, the binder resin may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and its various copolymers. Based on 100% by weight of the electrode active material layer, the content of the binder resin may generally be 1% by weight to 30% by weight or 1% by weight to 10% by weight.
[0060] In the present disclosure, if necessary, the electrode active material layer may include at least one additive of an oxidation stabilizer additive, a reduction stabilizer additive, a flame retardant, a heat stabilizer, or an antifogging agent.
[0061] The present disclosure provides a secondary battery having the above structure. The present disclosure also provides a battery pack including the secondary battery as a unit cell, a battery pack including the battery pack, and a device including the battery pack as a power source. In this case, the device may include any type of device that runs using electricity generated by an electric motor, for example, a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV); an electric two-wheeled vehicle, including an electric bicycle (E-bike) and an electric scooter (E-sccoter); an electric golf cart; and a power system, but is not limited thereto.
[0062] Hereinafter, the present disclosure will be described in more detail by way of examples. However, the following description describes the present disclosure by way of examples, and the scope of the present disclosure is not limited thereto.
[0063] Example 1
[0064] Lithium sulfide (Li2S, a product of Mitsuwa Chemical), phosphorus pentasulfide (P2S5, a product of Aldrich), lithium bromide (LiBr, a product of Aldrich) and lithium iodide (LiI, a product of Aldrich) were used as raw materials, weighed in an argon glove box and mixed using a mortar to obtain a mixture powder. The designed composition is (56.25+y)Li2S-18.75P2S5-15LiBr-10LiI, with an excess of Li2S so that y=0.14. The mixed powder was placed in a ZrO2 can together with ZrO2 balls, and then sealed to obtain an airtight can. The airtight can was mounted on a planetary ball mill, ball milled at 500rpm for 20 hours, the can was opened in a glove box, and the powder was collected. The powder was placed in a carbon crucible, which was then sealed and sintered in an argon flow at 200°C for 3 hours. The sintered powder was collected to obtain a solid electrolyte.
[0065] Example 2
[0066] As shown in Table 1, a solid electrolyte was obtained in the same manner as in Example 1, except that the amount y of Li2S added in excess was 0.28.
[0067] Example 3
[0068] As shown in Table 1, a solid electrolyte was obtained in the same manner as in Example 1, except that the amount y of Li2S added in excess was 0.56.
[0069] Example 4
[0070] As shown in Table 1, a solid electrolyte was obtained in the same manner as in Example 1, except that the amount y of Li2S added in excess was 1.22.
[0071] Example 5
[0072] As shown in Table 1, a solid electrolyte was obtained in the same manner as in Example 1, except that the amount y of Li2S added in excess was 1.69.
[0073] Comparative Example 1
[0074] As shown in Table 1, no excess Li2S was added. That is, a solid electrolyte was obtained in the same manner as in Example 1 except that the amount y of the excess added Li2S was 0.
[0075] Comparative Example 2
[0076] As shown in Table 1, a solid electrolyte was obtained in the same manner as in Example 1, except that the amount y of Li2S added in excess was 2.25.
[0077] [Table 1]
[0078]
[0079] [Evaluate]
[0080] The following evaluations were performed using the obtained solid electrolyte.
[0081] (XRD measurement)
[0082] A predetermined amount of solid electrolyte was placed on a stand in a hermetically sealed argon glove box and subjected to XRD measurement.
[0083] (Lithium ion conductivity measurement)
[0084] A predetermined amount of solid electrolyte is placed in In the tube, a single screw press is used in combination with The tube and pellet molding fixture (upper pressing pin and lower pressing pin) are pressed at 5MPa. Subsequently, a predetermined amount of gold powder is placed on both sides of the pellets and pressed at 7.5MPa by a single screw press to obtain The obtained The tube core is mounted on a fixture unit for electrochemical measurement, and a torque wrench is used to apply a maximum torque of 5.0 N·m to obtain a lithium ion conductivity measurement unit. The obtained lithium ion conductivity measurement cell is connected to an impedance meter to measure the resistance of the solid electrolyte pellets at room temperature (298K) and atmospheric pressure (1atm), and is used to determine the lithium ion conductivity [mS / cm] of the solid electrolyte.
[0085] (Raman spectroscopy)
[0086] A predetermined amount of solid electrolyte was placed in a hermetically sealed holder and Raman spectroscopy was performed (Lambda Vision, MicroRAM, using a laser with an excitation wavelength of 532 nm). -1 Up to 400cm -1 P2S6 detected at 4- The presence and intensity of the peak I1, as well as the peak at 415 cm -1 Up to 425cm -1 PS4 detected at 3- The presence or absence of the peak and its intensity I2 were evaluated, and the peak intensity ratio I1 / I2 was evaluated. The peak intensity is based on the peak height.
[0087] [Evaluation results]
[0088] (Crystalline Phase)
[0089] Figure 1 The XRD pattern obtained by XRD measurement is shown in FIG. Figure 1As shown, in Examples 1 to 5 and Comparative Examples 1 and 2, peaks derived from the type II crystalline phase in the sulfo-LISICON region were observed at 2θ=20.3±0.5°, 23.5±0.5°, and 29.6±0.5°, confirming that a glass-ceramic sulfide-based solid electrolyte was obtained. Other peaks observed in the XRD pattern may be derived from other crystalline phases and raw materials, namely Li2S, P2S5, LiBr, and LiI.
[0090] (Lithium ion conductivity)
[0091] Table 1 shows the measurement results of lithium ion conductivity. Figure 2 The dependence of lithium ion conductivity on composition is shown. Figure 2 In the figure, the horizontal axis represents the amount y of Li2S added in excess in the designed composition (56.25+y)Li2S-18.75P2S5-15LiBr-10LiI, and the vertical axis represents the lithium ion conductivity. As shown in Table 1, in Examples 1 to 5, the lithium ion conductivity is 2.6mS / cm to 5.5mS / cm. On the other hand, in Comparative Example 1 in which Li2S is not added in excess, the lithium ion conductivity is 2.3mS / cm, and in Comparative Example 2 in which the amount y of Li2S added in excess is 2.25, the lithium ion conductivity is 0.9mS / cm. By adding Li2S in excess in a specific amount, the lithium ion conductivity is increased. In particular, in Example 2 in which the amount y of Li2S added in excess is 0.28, the highest lithium ion conductivity of 5.5mS / cm is exhibited. It has been demonstrated that the lithium ion conductivity of the solid electrolyte is improved by increasing the molar ratio of Li2S to P2S5 to slightly above 3.
[0092] (Raman spectroscopy)
[0093] Figure 3 The Raman spectra of Example 2 and Comparative Examples 1 and 2 are shown. In all samples, the Raman spectra at 415 cm -1 Up to 425cm -1 PS4 detected 3- On the other hand, in Comparative Examples 1 and 2, at 380 cm -1 Up to 400cm -1 P2S6 detected at 4- , but this peak was not detected in Example 2 showing high lithium ion conductivity. Although not shown, in Examples 1 and 3 to 5, the peak at 380 cm -1 Up to 400cm -1 P2S6 detected 4- peak.
[0094] Table 1 shows the P2S6 obtained by Raman spectroscopy 4- Peak intensity I1 and PS4 3-The peak intensity ratio I1 / I2 of the peak intensity I2. In Example 2 showing high lithium ion conductivity, no P2S6 was detected. 4- The peak intensity ratio I1 / I2 is substantially zero (NA). In Examples 1 and 3 to 5 and Comparative Example 2 in which Li2S is excessively added, the peak intensity ratio I1 / I2 is 0.06 to 0.1, and in Comparative Example 1 in which Li2S is not excessively added, the peak intensity ratio I1 / I2 is 0.08. In Example 2 in which y=0.28, the lithium ion conductivity is significantly improved. Without being bound by theory, it is believed that the S provided by the excess Li2S fills the gap presumably due to the P2S6 4- The S vacancies are responsible for the formation of the skeleton structure, thereby improving the lithium ion conductivity.
[0095] Although the present disclosure has been described above with a limited number of embodiments and drawings, the present disclosure is not limited thereto, and it is apparent to those skilled in the art that various modifications and changes may be made within the technical scope of the present disclosure and the appended claims and their equivalents.
Claims
1. A sulfide solid electrolyte comprising: Sulfo-LISICON zone II crystalline phase, in, The sulfide solid electrolyte is glass ceramic, The sulfide solid electrolyte is represented by the chemical formula (100-x){(0.75+y / (100-x))Li2S-0.25P2S5}-xLiHa, Wherein, in the chemical formula, Ha is at least one selected from halogen elements, and Among them, 15≤x≤30 and 0 <y<2.25。 2. The sulfide-based solid electrolyte according to claim 1, wherein x satisfies 23≤x≤27.
3. The sulfide-based solid electrolyte according to claim 2, wherein y satisfies 0.2 <y<0.4。 4. The sulfide-based solid electrolyte according to claim 3, wherein Ha includes Br.
5. The sulfide-based solid electrolyte according to claim 1, wherein Satisfy I1 / I2<0.06, Among them, I1 is the wavelength at 380 cm in the Raman spectrum. -1 Up to 400cm -1 The intensity of the peak detected at 415 cm in the Raman spectrum is I2. -1 Up to 425cm -1 The intensity of the peak detected at .
6. A method for preparing the sulfide-based solid electrolyte according to claim 1, the method comprising: mixing a lithium source, a phosphorus source, a sulfur source, and a halogen source to obtain a mixture; as well as The mixture is sintered at a temperature of 150°C to 250°C.
7. An all-solid-state battery, comprising: positive electrode, negative electrode and solid electrolyte layer, The solid electrolyte layer comprises the sulfide-based solid electrolyte according to claim 1.
Citation Information
Patent Citations
Method of producing sulfide solid electrolyte material
JP2015011898A
Production method of sulfide solid electrolyte
JP2017100907A
Travel reservation information input system
JP2023023528A
Metal element-containing sulfide-type solid electrolyte and method for producing same
WO2019098245A1